Short Introduction to Standard and NonStandard Neutrosophic Set and Logic (review paper) - Florentin Smarandache (Neutrosophic Sets and Systems)
The definitions of Single-Valued Neutrosophic Set (SVNS), Interval-Valued Neutrosophic Set (IVNS), Subset-Valued Neutrosophic Set (SVNS), and respectively NonStandard Neutrosophic Set [Single-Valued (NoS SVNS), Interval-Valued (NoS IVNS), and Subset-Valued (NoS SVNS)], are recalled together with their operators. Similarly for Standard and NonStandard Neutrosophic Logic.